Deconstructing LajjA as a Marker of Indian Womanhood. (March 2013) - Sinha, Mala; Chauhan, Vishal
This article explores the meaning of lajjA as a core Indian cultural concept and how it enters the construction of womanhood in modern India. It discusses how the concept is embedded in India's social, political and ideological history and its psychological, social and behavioural representations. Written narratives, conversations, and symbolic representations of lajjA in films, advertisements and media were the primary source of data for deconstructing the concept. Findings showed that natured or denatured lajjA is represented as a virtue, emotion or tool of manipulation, depending on how it plays out in a particular situation. The proposed theoretical model in the paper links lajjA with the Guna theory from Bhagavad Gita to increase the explanatory power of the cultural concept, so that its impact on the well-being of individuals and social cohesion can be understood better.